Potensi Ekstrak Daun Singkong (Manihot esculenta Crantz) dalam Menurunkan Jumlah Sel Radang pada Tikus Periodontitis - Putri Alisah (Fakultas Kedokteran Gigi, 2026)
Periodontitis is a chronic inflammatory disease affecting the supporting tissues of the teeth and is primarily caused by anaerobic Gram-negative bacteria such as Porphyromonas gingivalis. Excessive inflammatory responses characterized by increased infiltration of inflammatory cells, including neutrophils, macrophages, and lymphocytes, play a critical role in periodontal tissue destruction. Although mechanical therapy combined with antibiotics such as metronidazole is commonly used, long-term antibiotic use may lead to adverse effects and bacterial resistance. Therefore, alternative antibacterial and antiinflammatory agents derived from natural sources are needed. Cassava leaf (Manihot esculenta Crantz) contains bioactive compounds such as flavonoids, saponins, and tannins, which are known to possess anti-inflammatory and antibacterial properties. This study aimed to evaluate the antibacterial and antiinflammatory effect of cassava leaf extract in reducing the number of inflammatory cells in a rat model of periodontitis. This experimental laboratory study used a post test only control group design. Sixteen male Wistar rats were divided into four groups: normal control, negative control (induced with P. gingivalis), positive control (induced with P. gingivalis and treated with metronidazole), and treatment group (induced with P. gingivalis and treated with cassava leaf extract at a dose of 179.2 mg/kg body weight). Periodontitis was induced by injection of P. gingivalis into the gingival sulcus. Histological examination of gingival tissue was performed using hematoxylin eosin staining to evaluate the number of neutrophils, macrophages, and lymphocytes. The results showed that cassava leaf extract significantly reduced the number of inflammatory cells especially neutrophils compared to the negative control group and demonstrated comparable effects to metronidazole. In conclusion, cassava leaf extract exhibits potential antibacterial and antiinflammatory effects and may serve as an alternative adjunctive therapy for periodontitis.
:: Finalisasi Repositori File 3 Juni 2026_Kurnadi
Keywords: Manihot esculenta extract; periodontitis; inflammatory cells; Porphyromonas gingivalis; antibacterial; antiinflammatory